Internationalization of SMEs: The Influences of Motives and Internal Factors in Selecting Markets Entry Mode - Bibi Noraini, Mohd Yusuf (2010)
This project paper will be focusing only on how Small Medium Enterprise (SME's) companies decide to go abroad and select their mode of foreign market entry. For better understanding of this project paper topic, several questionnaires will be formulated on the concerns and focusing on the motives for internationalization, approaches to foreign market entry modes and influence of internal factors. All the data are collected from experienced personnel and officers that are directly involved in international market and having served in companies having international market department. The company or respondent that is choosen for this project paper work is HPA Food Industries Sdn. Bhd, located at Jejawi Dalam, Perlis. However, only one person who works as an Assistant Manager of Marketing and Public Relations of HPA Food Industries Sdn. Bhd., Mr Mohamad Kamal Bin Ismail was choosen as a sample for this study. A qualitative approach was the most likely suitable in order to provide the answers for this project paper because the purpose of this study is to examine motives and internal factors that impacts SMEs approach to select the mode of entry for their company. Direct interview is one of the methodologies to get accurate and specific data for this project paper. Secondary data also will be used in this paper such as web sites, administrative records and others. Internal triggers that influence SME's choosing mode of entry are perspective management and specific internal events. Only markets demand as an external trigger that significantly relates to this study topics compare to others includes competing company, trade associations and outside experts, are not related. Proactive factors that influence SME's decision to choose mode of entry includes managerial urge, unique product, marketing advantages and economies of scale. Reactive factors that positively relates to this paper work only involve risk diversifications but not external sales of seasonal product factors. SME's more are comfortable to use export as a first mode of entry and thereafter they expect to change to a more complex mode namely Foreign Direct Investments. In this study SME's use naive rules in choosing mode of entry but at the same time they also practice correct strategy rules to some extent. Three internal factors that positively relates to this paper work are company size, international experience and product.